The Effect Of Green Marketing And Corporate Social Responsibility On The Purchase Decision Of Le-Minerale Products In Smti Padang Vocational School Students - Zoriasih, Zoriasih; Tilawatil Ciseta Yoda (ADPEBI, 2024)
A purchase decision is an action that consumers really take in deciding or overcoming problems to buy an itemafter considering various alternatives that exist. There are several factors that affect consumers in purchasing decision-making behavior, including Green Marketing and Corporate Social Responsibility. The purpose of this study is to find outthe extent of the influence of Green Marketing and Corporate Social Responsibility on the decision to Purchase Le-Minerale Products in SMK SMTI Padang students. The research method used is a quantitative descriptive method. Thepopulation in this study is students of SMK SMTI Padang who make purchases of Le-Minerale products. The sample inthis study is 86 respondents. The data analysis technique in this study is multiple linear regression consisting of a partialtest (t-test), a simultaneous test (f-test), and a determinant coefficient (R-Square). The results of the Green Marketingvariable t-test, tcalculated > ttable or 2.540 > 1.663. with a significant value (sig=0.013 < 0.05) meaning that H1 wasrejected and H0 was accepted. Meanwhile, the Corporate Social Responsibility variable is calculated < ttable or 1.233 <1.663, with a significant value (sig=0.221 > 0.05) meaning that H2 is rejected and H0 is accepted. Based on the F test, it isknown that the value of f is calculated > f table or 12.198 > 3.103 and the significance of f = 0.000 < 0.05. This means thatH3 is accepted and H0 is rejected. This means that (simultaneously) the variables of Green Marketing and Corporate SocialResponsibility have a positive and significant effect on the purchase decision of Le-Minerale products in SMK SMTIPadang students.